Pharmacogenomic biomarkers of ACE inhibitor–induced cough in a multi-ethnic UAE cohort - Altoum, Sahar M.; Al-Mahayri, Zeina N.; Khasawneh, Lubna Q.; Alqasrawi, Mais N.; Dabaghie, Lilas; Hamza, Dana; Ali, Bassam R. (Frontiers in Pharmacology, 2025)
Background and objectivesAngiotensin-converting enzyme inhibitors (ACEIs) are widely used to manage hypertension and cardiovascular diseases. However, dry cough is a common side effect, affecting 5%–35% of patients and often leading to discontinuation. This study aimed to investigate genetic variants involved in ACEI-induced cough and ACE plasma levels in UAE multi-ethnic hypertensive patients.MethodThe study cohort was pragmatically selected from the larger EmHeart Study (n = 900), a UAE-based pharmacogenomic initiative. Patients prescribed ACEIs were screened for inclusion. This multi-center, retrospective exploratory study involved genotyping 107 patients treated with ACEIs, including n = 35 in the cough group and n = 72 in the non-cough group. Variants of ACE; rs1799752 I/D, BDKRB2; rs1799722 (C>T), and KCNIP4; rs7675300 (C>A), rs1495509 (T>C), rs7661530 (T>C), and rs16870989 (T>A) were genotyped using standard technologies. A sandwich ELISA was done to investigate the ACE plasma levels in our cohort.ResultsWe found that the ACE rs1799752 I/D genotype in the over-dominant model, was statistically significantly associated with ACEI-induced cough (p = 0.046) after adjusting for gender. Similarly, the T/T genotype of the KCNIP4 rs7661530 (T>C) variant was associated with significantly higher risk of cough compared to the combined C/C and T/C genotypes (p = 0.035). In contrast, the variants BDKRB2 rs1799722 (C>T), KCNIP4 rs7675300 (C>A), rs1495509 (T>C), and rs16870989 (T>A) were not significantly associated with ACEI-induced cough in our study. Moreover, ACE plasma levels were significantly lower in the cough group compared to the non-cough group (p = 0.0014). Stratified analysis by rs1799752 I/D genotypes revealed a significant difference within the I/D genotype (p = 0.0061), with higher levels in the non-cough group. No significant differences were found for the D/D or I/I genotypes.Conclusion and limitationsOur data showed a significant association between ACEI-induced cough and the ACE rs1799752 I/D genotype, as well as lower ACE plasma levels in the cough group. This is the first study in the UAE and Middle East to report such findings and include all these variants in a single analysis. Although the sample size is small, our results contribute cumulative evidence on the genetic predisposition to ACEI-induced cough among hypertensive patients.